Treatment with proton pump inhibitors increases the risk for development of hepatic encephalopathy after implantation of transjugular intrahepatic portosystemic shunt (TIPS) - Sturm, Lukas (United European Gastroenterol J, 2018)
BACKGROUND AND OBJECTIVE: Treatment with proton pump inhibitors (PPIs) has been associated with development of hepatic encephalopathy (HE). As development of HE is a major complication after implantation of a transjugular intrahepatic portosystemic shunt (TIPS), we hypothesized that PPI treatment may be associated with a higher risk of post-TIPS HE. METHODS: We analyzed data of 397 patients with liver cirrhosis who received de novo TIPS implantation at the University Medical Center Freiburg, Germany. We assessed whether PPI medication and other patient characteristics are predictive factors for the development of post-TIPS HE. RESULTS: Patients with PPI treatment at the time of TIPS implantation showed significantly higher rates of post-TIPS HE than those without PPI medication (30.4% vs 11.7%, p < 0.001). The rate of post-TIPS HE increased in a dose-dependent manner. However, PPI medication did not directly affect transplant-free survival. Remarkably, in 59.1% of patients who received PPIs there was no clear indication. CONCLUSIONS: PPI treatment may be an independent risk factor for the development of post-TIPS HE and the risk increases with PPI dose. Indication for PPI treatment should be assessed carefully prior to TIPS implantation in patients with liver cirrhosis.